Case Report: Unique management strategy for rare case of esophageal foreign body - Rustemov, Dastan; Bilal, Ruslan; Tukinov, Ruslan; Nekessov, Adilzhan; Dzhenalaev, Damir; Ermeshev, Erbulat; Mukhamedov, Zarip; Mustafinov, Dulat; Utebaliev, Ruslan; Sakuov, Zhenis; Kaliev, Baurzhan (Frontiers in Surgery, 2024)
Foreign bodies that enter the esophagus can cause serious complications that may require extensive surgical intervention, including open surgery. The treatment method depends on the location, size, configuration, and number of foreign bodies in the esophagus, but to date, the best method to remove foreign bodies from the esophagus remains uncertain. Foreign bodies which can damage the walls of esophagus varies from bones and bone fragments, to metallic objects and batteries. In this article, we present a rare case of a "fish bone" penetrating through the esophagus walls and directly punctured the aorta, forming a post-traumatic saccular pseudoaneurysm of the descending thoracic aorta, which was successfully treated with endovascular stent placement to the aorta and with endoscopic foreign body removal.We reported a case of a 16-year-old male with a 6-day history of chest pain after consuming fish. As result of immediate test in regional hospital using oral flexible esophagogastroduodenoscopy abnormalities were not reported. Due to persistence of beforementioned symptoms, a fiberoptic esophagogastroduodenoscopy was performed 3 days later, revealing a 1.5-2.0 cm long altered area with contact bleeding 33.0 cm from the incisors, but no visualization of any foreign body. Computed tomography revealed a fish bone that had completely passed through walls of the esophagus and punctured the aortic wall, forming an aneurysm. Patient was urgently hospitalized by air ambulance to our hospital for high-specialized medical intervention after 6 days. After the endovascular placement of a stent graft, the fish bone was successfully removed by endoscopic intervention. 12 months follow up showed no abnormalities.Endoscopic removal of foreign bodies in the esophagus and extracting a foreign body after thoracic endovascular aortic stent may be a feasible option for some cases.